1999
DOI: 10.1021/ac990372u
|View full text |Cite
|
Sign up to set email alerts
|

Microchip Flow Cytometry Using Electrokinetic Focusing

Abstract: Flow cytometry of fluorescently labeled and unlabeled latex particles is demonstrated on a microfabricated device. The latex particles were detected and counted using laser light scattering and fluorescence coincidence measurements. Sample confinement was accomplished using electrokinetic focusing at a cross intersection, and detection occurred 50 μm downstream from the intersection. Particles with diameters of 1 and 2 μm were analyzed and distinguished from each other based on their light scattering intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
186
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(191 citation statements)
references
References 26 publications
3
186
0
Order By: Relevance
“…A more robust approach, pioneered by Ramsey's group, 8,13,14 has been to confine the sample stream on either side with a particle-free aqueous solution. This design is simple and easily fabricated, leading several researchers to imitate it.…”
Section: Introductionmentioning
confidence: 99%
“…A more robust approach, pioneered by Ramsey's group, 8,13,14 has been to confine the sample stream on either side with a particle-free aqueous solution. This design is simple and easily fabricated, leading several researchers to imitate it.…”
Section: Introductionmentioning
confidence: 99%
“…Historically speaking, flow cytometry was the first technique to analyze individual subcellular particles [1], so it is not surprising that many of the first analyses of large populations of individual microparticles [2][3][4][5][6][7], cells [8,9], and subcellular particles [10] on microfluidic devices also used flow cytometry. Electrophoretic separation schemes have also been used since the first glass microfluidic devices were described by Manz et al [11] and Harrison et al [12,13] and they continue to be quite popular due to ease of application.…”
Section: Introductionmentioning
confidence: 99%
“…One example of a particularly important application is the development of a flow cytometer on a chip [1][2][3][4][5][6][7][8][9][10]. For such systems to work efficiently, it is important to be able to confine the sample into a small, spatially well-defined volume, giving as small a probe volume as possible for the detector.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobson and Ramsey [9] described a device which was microfabricated from etched glass and demonstrated two-dimensional confinement of molecules with applied voltages of 3 kV. Schrum et al [2] showed how electrokinetic focusing could be used to focus 0.97 mm and 1.94 mm diameter latex particles at velocities of 1 mm s -1 . Chou et al developed a device for detecting DNA molecules [10] and Fu et al [1,3] used a similar system to construct a microfabricated fluorescence activated cell sorter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation